A state estimator–based nonlinear predictive control for a fractional-order Francis hydraulic turbine governing system. (21st December 2019) - Tian, Yuqiang; Wang, Bin; Chen, Peng; Yang, Ying
A nonlinear predictive control scheme with a state estimator for a fractional-order hydraulic turbine governing system is studied in this article. First, a more practical fractional-order model of the hydraulic turbine governing system is introduced. Second, according to the Grünwald–Letnikov definition of fractional calculus, the fractional-order hydraulic turbine governing system is transformed into a nonlinear discrete model. Third, based on the Takagi–Sugeno fuzzy theory, a fuzzy prediction model of the fractional-order hydraulic turbine governing system is presented. Furthermore, a state estimator–based nonlinear predictive control scheme is proposed for the fractional-order hydraulic turbine governing system, and the controller gain can be obtained by solving a linear matrix inequality. Finally, experimental results show that the proposed state estimator–based nonlinear predictive control could effectively restrain the oscillation of the fractional-order hydraulic turbine governing system under various working conditions.